Aftrede as integrasionele taak - Brunsdon, A. R. (Koers, 2008)
Retirement as integrational task In this article, the stance is taken that retirement can be viewed as a critical life phase. Depending on how retirees cope with this phase, they can either experience feelings of futility or engage in an optimal use of this promising period. The critical task of the retirement phase could therefore be outlined as achieving a deep sense of fulfillment and optimisation of lifeopportunities during the so-called golden years. This article will explore retirement as integrational task, the challenge being to guide retirees to an integration of life and faith experiences in order to experience meaning. A narrative approach to pastoral care is suggested as a mode for integration as it takes the generated experiences (stories) of people seriously. Within a reformational view of the narrative the Word of God is also taken seriously. In this fusion between the Story of God and man’s story lies the integration which will result in the creation of meaning during the final stage of man’s journey through life.